Need to revitalize grazing resource management practices for sustainable use of forage in arid Rajasthan - Prasad, Rajendra; Mertia, R.S.; Chaturvedi, O.P.; Tewari, R.K.; Shukla, Ashok; Singh, Prashant (Indian Journal of Agroforestry, 2020)
Since ages, the traditional grazing grounds have been the lifeline of pastoral economy in arid region of Rajasthan. Owing to many fold increase in the human and livestock populations, these grazing grounds have been subjected to excessive pressure of grazing and utilization. As a results the area under traditional grazing resources – gochar, oran, beers, jorh, adaw, bhelwars or choili, etc. have declined. Due to over-grazing, most of such grazing resources are in degraded form with poor productivity. The traditional management practices of grazing resources by the community at village level with the system of kar and/or go-had (grazing boundaries) have also disappeared. The continuous decrease in grazing resources and increase in livestock population coupled with changing cropping patterns lead to conflicts between pastoral v/s herders and herders v/s farmers. The alarming situation warrants to look in to the opportunities- protection, reseeding, scientific grazing management which allows resting period to grasslands/pasture, integrating silvi-pasture systems and the issues-free grazing, herd size linked with equity on community grazing land, pastoral migration, etc. for conservation and rehabilitation of pastures and other grazing resources in arid region. Sensitization of people and capacity building at village level to ensure peoples participation, development of grazing calendar, establishment of fodder banks and formulation of a grazing policy like revenue policies both at State and National level would augment not only forage productivity of these shrinking grazing resources and enthuse their better management on sustainable basis but would also lead to better management of grazing resources with community participation.